Storytelling Methods In Islamic Cultural History Learning: A Systematic Literature Review On Students’ Learning Interest - Muhammad Hori; Siti Zaenab Raihanah; Jasmansyah Faizza; Irfan Sofian; Ia Hidarya (Universitas Sulawesi Barat, 2026)
This study investigates the utilization of storytelling techniques in the instruction of Islamic Cultural History (SKI) and their correlation with students’ learning interests. History education is frequently regarded as monotonous and less engaging due to intricate content, teacher-centered delivery, rote memorization practices, and limited contextual presentation. These factors contribute to students’ diminished interest in learning SKI. Consequently, innovative pedagogical approaches are necessary to make learning more meaningful and captivating. This research employed a Systematic Literature Review (SLR) by analyzing twenty articles published between 2019 and 2025 sourced from Google Scholar, Scopus, and SINTA databases. Articles were selected based on inclusion and exclusion criteria pertinent to storytelling methodologies, SKI learning, and students’ learning interests. The chosen studies were analyzed thematically to identify key findings and emerging research trends. The review identified three primary findings: (1) storytelling enhances students’ attention and emotional engagement, (2) storytelling facilitates a contextual and meaningful comprehension of historical content, and (3) its effectiveness is contingent upon teachers’ pedagogical competence, media support, and integration with other learning strategies. In summary, storytelling presents a promising approach for boosting students’ interest in learning SKI and elevating the quality of history education.